Construction of plate‐like magnetic heterostructure for synergistic microwave absorption. Issue 1 (10th September 2022) - Ma, Jiaxin; Wang, Jiancheng; Hu, Xiaobo; Wang, Lianjun; Fan, Yuchi; Jiang, Wan
Abstract: The dramatically dropped permeability of magnetic materials at gigahertz frequencies, known as the Snoek's limit, has severely constrained the microwave absorbing performance of magnetic materials. To break the Snoek's limit at high frequencies, a plate‐like magnetic heterostructure composed of Ni‐Fe ferrite, nitride, and Permalloy is fabricated through nitridation of Ni‐Fe layered double hydroxide. It has been found that single‐phase magnetic flakes or the multi‐phase heterostructure with extraordinarily linked magnetic nanoplates can be obtained by simply adjusting the temperature of nitridation. Due to the highly anisotropic morphology and synergistic effect at abundant heterogeneous interfaces, the magnetic heterostructure shows enhanced imaginary permeability that is even higher than that of single‐phase Permalloy. Accordingly, the magnetic loss in C and X bands is improved, leading to significant enhancement of attenuation constant in this novel microwave absorber. Combined with the moderate permittivity, the impedance matching of the heterostructure is superior compared to every single component, as well as the mixture of these components. As a result, the minimum reflection loss of −59.30 dB at a thickness of 2.02 mm and effective absorption bandwidth (RL<−10 dB) of 2.44 GHz is realized. These findings provide a novel path to designing high‐performance microwave absorbers based on magnetic materials.